'Clean, Fix, and Grant Splendor': The Making of Diccionario de Autoridades. (27th August 2021) - Stavans, Ilan
Abstract: Hailed as the foundation of modern Spanish-language lexicography, the Diccionario de Autoridades was developed over a period of thirteen years. While it is a window to appreciate the impact of Enlightenment ideas in Spain, it also showcases some of the country's most entrenched phobias, both within and throughout its colonies across the Atlantic. This essay looks at its planning, structure, and publication in political, cultural, and linguistic terms. It analyses its legacy over the Dicionario de la Lengua Española, which is the organ of the Real Academia Española and on other Spanish-language lexicons. And it compares it with the work of Samuel Johnson's A Dictionary of the English Language and Noah Webster's An American Dictionary of the English Language . The xenophobic motto of the Real Academia Española, 'Clean, Fix, and Grant Splendor', long a subject of controversy, is the philosophy behind Autoridades .